(untitled) (The Strategic Review for Southern Africa, 2020)
This article focuses on the question of South African decolonisation with particular reference to the Afrikaners as both the colonised and the coloniser. It is argued that Afrikaners winning state power in 1948 became something of an ironic blueprint for African post-colonial countries — nominally independent and free, but in reality still colonies. The enduring colonial characteristics of South Africa are briefly discussed, and how Afrikaner- and African nationalists in power turned out to be variations of a post-colonial pattern. Language is discussed as a focal point of this pattern since 1948, also with regards to the 2015 student revolts at South African universities. In conclusion some proposals are offered about what decolonisation should be, and what universities can contribute to it.